Direct metal manufacturing - Bollinger, Steven R.; Rembiesa, David; Grimm, Todd (Manufacturing insights)
This program explores advancements in direct metal manufacturing and shows how these technologies affect the creation of parts and tooling in various metals. It also demonstrates the current state of direct metal manufacturing processes and illustrates what happens when innovative companies capitalize on direct metal manufacturing to make dramatic changes to the way parts and tooling are designed.